2014
DOI: 10.3109/09273948.2014.894084
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Persistent Corneal Epithelial Defects: A Standardized Approach Using Continuous Wear PROSE Therapy

Abstract: Continuous wear of a PROSE device, using a strictly standardized regimen, constitutes an effective, safe treatment option for refractory persistent epithelial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…Cressey et al, demonstrated resolution of vascularized limbal keratitis similar to the appearance of the present case [18]. Resolution of recalcitrant persistent epithelial defects have also been observed with PROSE treatment suggesting that there is a beneficial and therapeutic effect conferred onto the ocular surface with PROSE devices or scleral lenses [19][20][21].…”
Section: Discussionsupporting
confidence: 76%
“…Cressey et al, demonstrated resolution of vascularized limbal keratitis similar to the appearance of the present case [18]. Resolution of recalcitrant persistent epithelial defects have also been observed with PROSE treatment suggesting that there is a beneficial and therapeutic effect conferred onto the ocular surface with PROSE devices or scleral lenses [19][20][21].…”
Section: Discussionsupporting
confidence: 76%
“…Ciralsky et al have described a scleral lens care regime for extended wear in compromised corneas; daily removal, cleaning and reinsertion with replacement of the reservoir fluid with an antibiotic drop [30]. In this case series the scleral lenses are worn on eyes without severe ocular surface disease and none developed infectious keratitis.…”
Section: Discussionmentioning
confidence: 93%
“… 1 As shown herein, conservative treatments such as topical lubricants, autologous serum, bandage contact lens, and tarsorraphy failed to treat these corneal epithelial defects. Although refractory cases can be benefited by scleral contact lens, 29 its use was limited in patients as illustrated in this study due to the presence of significant symblepharon. Similarly, placement of PROKERA could not be instituted due to symblepharon in three of four patients.…”
Section: Discussionmentioning
confidence: 94%